Visionary Leadership of School Principles: Analysis Based on Managerial Competence and Financial Literacy at Senior High School in Pekanbaru - Azhar Azhar; Daeng Ayub Natuna; Try Wahyuni (STAI Hubbulwathan Duri, 2023)
A leader who is focused on the future can create, formulate, communicate, socialise, transform, and implement creative and innovative ideas and mobilise the organization's power and potential to achieve goals. This study examines how management competency affects Pekanbaru City High School's visionary leader. This quantitative study will use ex post facto research to examine the impact of financial literacy and managerial competence on the visionary leadership of Pekanbaru City High School's head. This study's population is 88 and its sample is 73. This study collects data via questionnaire. This study uses descriptive and inferential statistics. For descriptive statistical analysis, this study uses Microsoft Excel and SPSS version 253 for Windows in-process data. The results of this investigation imply that. (1) The principal of SMA Pekanbaru (Y) is influenced by managerial competence (X1), (2) by financial literacy (X2), and (3) by the combination of the two. Visionary leadership requires managerial and financial literacy. Principals must be independent in developing their awareness of available technologies and information and then must be more precise in making decisions to advance education by implementing school quality improvement programs.